Study Of Tensions And Strains Of The Partial Removable Dentures Retained By Cast Clasps - Paul Barsanescu; Oana Tanculescu; Norina Forna; Monica Andronache (Romanian Society of Oral Rehabilitation, 2011)
The practical work in the field of dentistry offers a clear picture of the increased frequency of therapeutic solutions on the partially edentulous, aiming through it a high degree of biological recovery, a particularly important role being for knowledge of the spreading tensions on the remaining prosthetic field elements and for the induced strains distribution in the removable prosthetics substitutes. The analysis of biomechanical behavior of the removable partial dentures, as well as the body's response to the induced action of it, are an important parts of the current studies with results of particular importance in choosing the final therapeutic solution.